F+DCL?DF+CL REAKSİYONUNDA CORIOLIS ETKİSİNİN ZAMANA BAĞLI KUANTUM DALGA PAKETİ METODU İLE İNCELENMESİ - KARIŞMAZ, BELGİN (Fırat Üniveristesi, 2012)
Bu tez çalışmasında, D+FCl potansiyel enerji yüzeyi kullanılarak reaksiyon dinamikleri ve kinetikleri akı analizi metodu kullanılarak araştırıldı. Centrifugal Sudden yaklaşımı kullanılarak, eşik enerjisinden 0.8 Ev çarpışma enerjisine kadar toplam açısal momentum kuantum sayısı J=0 için reaksiyon ihtimaliyetleri elde edildi. Toplam açısal momentumun belli değerleri için J=10,20,....130'a kadar, Centrifugal Sudden ve Coriolis Coupling metotları kullanılarak toplam reaksiyon ihtimaliyetleri ve integral tesir kesitleri hesaplandı.Anahtar Kelimeler: Reaksiyon ihtimaliyetleri, İntegral tesir kesitleri.

The Investigation of the Coriolis Effect on the F+DCI+DF+CI Reaction By Means of Quantum Wave Packet MethodIn this master thesis, reaction dynamics and kinetics have been investigated on a D+FCl potential energy surface by using a flux analysis method. Total reaction probabilities have been obtained by using Centrifugal sudden approximation from threshold up to 0.8 eV collision energy at total angular momentum J=0. Total reaction probabilities at selected total angular momentum quantum number J=10,20,30,?130 at a step of 10 have been calculated using Centrifugal sudden approximation and Coriolis coupling methods and integral cross-sections obtained from the total reaction probabilities using an interpolation method.Key Words: Reaction probabilities, Integral cross-sections.
The investigation of the coriolis effect on the f+dci+df+ci reaction by means of quantum wave packet method
Keywords: Fizik ve Fizik Mühendisliği